The genetic basis of variation in thermal plasticity in Drosophila melanogaster - Crawford, Paul Joseph (Kansas State University, 2013)
The organismal response to temperature represents one of the most ubiquitous processes that occur in the natural world, and this response is critical for survival in most habitats. Increased attention should be focused on how organisms cope with temperature extremes, either through adaptation, plasticity, or a combination of both, as climate models predict increased variations in temperature accompanied by novel thermal extremes. Drosophila melanogaster is an excellent resource for answering questions pertaining to how organisms persist in environmental extremes because they originated in central tropical Africa and have since colonized nearly the entire globe, exposing them to many novel thermal stressors. In this work I elucidated regions of the genome contributing to phenotypic variation in cold tolerance and thermal plasticity. A quantitative trait locus (QTL) approach was used, which involved phenotyping roughly 400 recombinant inbred lines (RILs) of D. melanogaster from the Drosophila Synthetic Population Resource (DSPR). The DSPR captures genetic variation from around the globe, allowing for precision mapping of cold tolerance and thermal plasticity QTL, while simultaneously determining the frequency of the QTL alleles. Upon development at both 18°C and 25°C, RILS were measured for a common cold tolerance metric, chill-coma recovery time (CCR), and a plasticity value was derived as the change in CCR between environments. Analysis of variance revealed significant effects of sex, line (RIL), treatment (temperature), and line by treatment interaction (GxE). Mapped QTL for chill-coma recovery time at 18°C and 25°C spanned the same regions as several studies previously reported, validating the automated phenotyping method used and the mapping power of the DSPR. QTL between CCR at 18°C and 25°C overlapped significantly, and QTL for thermal plasticity shared the similar regions as QTL for CCR, but also exhibited two non-overlapping QTL on the left arm of the third chromosome. This study demonstrated the tremendous amount of variation present in cold tolerance phenotypes and identified candidate regions of the genome that contribute to thermal plasticity and require further investigation.
Keywords: Plasticity; Quantitative trait locus; Drosophila; Temperature; Biology (0306); Genetics (0369)